2003
DOI: 10.1021/la035126z
|View full text |Cite
|
Sign up to set email alerts
|

Organization and Dynamics of Melittin in Environments of Graded Hydration:  A Fluorescence Approach

Abstract: Melittin is a cationic hemolytic peptide composed of 26 amino acid residues. It is intrinsically fluorescent because of the presence of a single tryptophan residue which has been shown to be crucial for its hemolytic activity. We have previously shown that the sole tryptophan of melittin is located in a motionally restricted region in the membrane and the tryptophan environment is modulated in the presence of negatively charged phospholipids. Reverse micelles represent a type of organized molecular assembly wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
72
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 57 publications
(75 citation statements)
references
References 106 publications
3
72
0
Order By: Relevance
“…Furthermore, the magnitude of REES (0-6 nm) suggests that there is a considerable difference in the relaxation of solvent molecules (dynamics of hydration) in different positions of the outer vestibule of KcsA. It has been shown that a change of a few nanometers in REES is significant, and the observed changes in the magnitude of REES (0-6 nm) in our case fall within the range of expected REES changes (∼5 nm) associated with changes from fully restricted to freely relaxing environments (24,25). It should be mentioned that REES does not generally provide a quantitative estimate of the water relaxation dynamics because the magnitude of REES is not always linear and is dependent on the given system under investigation (22).…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…Furthermore, the magnitude of REES (0-6 nm) suggests that there is a considerable difference in the relaxation of solvent molecules (dynamics of hydration) in different positions of the outer vestibule of KcsA. It has been shown that a change of a few nanometers in REES is significant, and the observed changes in the magnitude of REES (0-6 nm) in our case fall within the range of expected REES changes (∼5 nm) associated with changes from fully restricted to freely relaxing environments (24,25). It should be mentioned that REES does not generally provide a quantitative estimate of the water relaxation dynamics because the magnitude of REES is not always linear and is dependent on the given system under investigation (22).…”
Section: Resultssupporting
confidence: 78%
“…22 and 23 for reviews and SI Materials and Methods for details). Because REES provides information on the relative rates of water relaxation dynamics (24,25), it is sensitive to changes in local hydration dynamics. environment.…”
Section: Resultsmentioning
confidence: 99%
“…It has thus been shown that the magnitude of REES for melittin bound to reverse micelles is sensitive to the change in water content of the system. 151 This constitutes the first report directly demonstrating that REES is sensitive to the changing dynamic hydration profile of an amphiphilic peptide. In another study, the magnitude of REES of membrane-bound melittin has been shown to be dependent on the extent of lipid chain unsaturation in the membrane.…”
Section: Monitoring Protein Structure and Dynamics By Rees 209mentioning
confidence: 78%
“…57 An even larger REES of 4-8 nm, corresponding to the excitation wavelength range 280-307 nm, was observed for melittin incorporated in reverse micelles of sodium bis (2-ethylhexyl) sulfosuccinate (AOT) that are formed in hexane solvent. 48 However, the dissimilarity of hexane and aqueous solvents makes difficult the comparison of the results reported in ref 48 and herein.…”
Section: Comment On the Role Of Micelle And Cluster Formation In Helimentioning
confidence: 90%
“…The wavelength of maximum fluorescence emission for a polar fluorophore in a viscous solution or condensed phases with motionally restricted environments has been observed to shift to the red as the excitation wavelength is shifted toward the red edge of the absorption band. [48][49][50][51][52][53][54][55] This REES phenomenon occurs when the dipolar relaxation time for the solvent shell surrounding the fluorophore becomes comparable to or longer than the fluorescence lifetime. As an example, it is known that when melittin is bound to bilayer membranes, it is localized in the motionally restricted interfacial region of the membranes.…”
Section: Comment On the Role Of Micelle And Cluster Formation In Helimentioning
confidence: 99%